2022
DOI: 10.1186/s12937-022-00821-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Penn Healthy Diet screener with reference to adult dietary intake data from the National Health and Nutrition Examination Survey

Abstract: Background There is a need for a feasible, user-friendly tool that can be employed to assess the overall quality of the diet in U.S. clinical settings. Our objectives were to develop the Penn Healthy Diet (PHD) screener, evaluate screener item correlations with Healthy Eating Index (HEI)-2015 components, and develop a simple scoring algorithm. Methods National Health and Nutrition Examination Survey (NHANES) 2017–18 dietary recall data in adults we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Using the simple scoring algorithm recently published (19) , in respondents to both the PHD and the ASA24, the PHD score was 14·5 ± 4·68 and the HEI-2015 score based on ASA24 data was 52·7 ± 16·5. The screener score exhibited a moderate correlation with the HEI-2015 total score ( r = 0·59, P = 0·0034).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the simple scoring algorithm recently published (19) , in respondents to both the PHD and the ASA24, the PHD score was 14·5 ± 4·68 and the HEI-2015 score based on ASA24 data was 52·7 ± 16·5. The screener score exhibited a moderate correlation with the HEI-2015 total score ( r = 0·59, P = 0·0034).…”
Section: Resultsmentioning
confidence: 99%
“…There is substantial need for more efficient and user-friendly methods to gauge diet quality. We developed the PHD screener to help meet this need (19) . In this study, we demonstrated that the patient experience of the PHD screener was generally positive, and the time to completion was in the range expected for a dietary screener.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies of 11 screeners for assessing diet quality based on FBDGs were included in the review. Four screeners were developed in the USA [74][75][76][77][78], three in Australia [79][80][81][82], three in northern Europe [83][84][85] and one in Switzerland [86]. The studies on the Penn Healthy Diet Screener (PHDS) [74], Picture your Plate (PYP) [75] and the Score d'Alimentation Saine (SCASA) [86] were conducted between 2020 and 2022; the studies on the residential environments dietary guideline index (RDGI) [79], the Short Food Survey (SFS) [80], the Australian Recommended Food Score (ARSF) [81,82], the fifteenitem Food Frequency Questionnaire (15-item FFQ) [83] and the Food-Based Diet Quality Score (FBDQS) [84] were between 2015 and 2019; and the Index of Diet Quality (IDQ) was studied in 2010 [85].…”
Section: Characteristics Of the Included Screenersmentioning
confidence: 99%